Antioxidant, Antibacterial and Anticancer Performance of Reduced Graphene Oxide Prepared via Green Tea Extract Assisted Biosynthesis. Issue 33 (3rd September 2020) - Vatandost, Elham; Saraei, Azade Ghorbani‐Hasan; Chekin, Fereshteh; Raeisi, Shahram Naghizadeh; Shahidi, Seyed‐Ahmad
Abstract: Green tea extract (GTE) contains polyphenols and can play as a bioreducing and stabilizing agent. This paper describes environmentally friendly approach for synthesis of reduced graphene oxide using GTE (GTE‐rGO). The results have confirmed that biomolecules present in green tea extract not only act as bioreductant but also functionalize the surface of rGO due to hydrogen binding and π‐π stacking interactions. The 100 ppm of rGTE‐rGO showed 0.68 ppm phenols and 0.24 ppm flavones. The rGTE‐rGO was found to have highest % of 2, 2‐diphenyl‐1‐picrylhydrazyl (DPPH, 73.83 %) scavenging activity. Antibacterial activity of GTE‐rGO exhibited strong activity against Escherichia coli and Staphylococus. A cytotoxicity evaluation of GO and GTE‐rGO was carried out on fibroblast, MCF7 breast cancer and PC3 prostat cancer cells. The 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide (MTT) results showed high viability loss and toxicity of GTE‐rGO against cells especially for PC3 cells. Thus, GTE‐rGO because of biomolecules present could potentially act as antioxidant, anticancer and antibacterial agent. Abstract : The reduced graphene oxide (rGO) was synthesized employing green tea extract (GET) as a reducing and stabilizer agent. The antioxidant capacity was proven to be high (73.83 %). The antibacterial activity of GTE‐rGO confirmed that GTE‐rGO is a very effective antibacterial agent against Staphylococcus aurous. MTT result against PC3 and MCF7 showed high toxicity of GTE‐rGO against cells especially for PC3. The GTE‐rGO contains amounts of biomolecules, proving perfect antioxidant, antibacterial and anticancer agent.